2021
DOI: 10.1017/jpa.2021.5
|View full text |Cite
|
Sign up to set email alerts
|

Early Miocene coral reef-associated bryozoans from Colombia. Part I: Cyclostomata, “Anasca” and Cribrilinoidea Cheilostomata

Abstract: This is the first of two comprehensive taxonomic works on the early Miocene (ca. 23–20 Ma) bryozoan fauna associated with coral reefs from the Siamaná Formation, in the remote region of Cocinetas Basin in the La Guajira Peninsula, northern Colombia, southern Caribbean. Fifteen bryozoan species in 11 families are described, comprising two cyclostomes and 13 cheilostomes. Two cheilostome genera and seven species are new: Antropora guajirensis n. sp., Calpensia caribensis n. sp., Atoichos magnus n. gen. n. sp., G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 83 publications
(155 reference statements)
1
17
0
Order By: Relevance
“…Some works point to a late Oligocene age (Rollins, *Corresponding author 1965;Cardenas et al, 2020;Jaramillo et al, 2020), while others suggest a diachronic deposition that reached the early Miocene (Duque-Caro, 1974;Teatin, 1991;Silva-Tamayo et al, 2017). Here, we follow Flórez (2020) and Flórez et al (2021) who suggested an early Miocene age based on larger benthic foraminifera, and the dating provided by Silva-Tamayo et al (2017) based on strontium isotopes of coralline algae from the same localities studied here. A revision of the lateral facies change, within the early Miocene, is needed in some parts of the Cocinetas Basin to understand the stratigraphic relationships between the Siamaná and Uitpa formations and clarify the age of the last onlapping phases of the former; however, this is beyond the scope of the present work.…”
Section: Geologic Settingsupporting
confidence: 78%
See 4 more Smart Citations
“…Some works point to a late Oligocene age (Rollins, *Corresponding author 1965;Cardenas et al, 2020;Jaramillo et al, 2020), while others suggest a diachronic deposition that reached the early Miocene (Duque-Caro, 1974;Teatin, 1991;Silva-Tamayo et al, 2017). Here, we follow Flórez (2020) and Flórez et al (2021) who suggested an early Miocene age based on larger benthic foraminifera, and the dating provided by Silva-Tamayo et al (2017) based on strontium isotopes of coralline algae from the same localities studied here. A revision of the lateral facies change, within the early Miocene, is needed in some parts of the Cocinetas Basin to understand the stratigraphic relationships between the Siamaná and Uitpa formations and clarify the age of the last onlapping phases of the former; however, this is beyond the scope of the present work.…”
Section: Geologic Settingsupporting
confidence: 78%
“…These coral communities thrived in tropical waters, at depths of 2-30 m, with low turbidity, low energy, and limited siliciclastic input (Flórez et al, 2019a, b;Flórez, 2020). Associated with them, we found 32 bryozoan species (Flórez et al, 2021;this paper). New species account for 31% (10 species) of the whole assemblage.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations